Root border cells: A pioneer’s of plant defence in rhizosphere - K, DARSHAN; SINGH, JAGMOHAN; YADAV, SURESH; M, VENUGOPALA K; AGGARWAL, RASHMI (The Indian Journal of Agricultural Sciences, 2020)
The environment around the root in rhizosphere is a complex region where multiple interactions take place among soil, plant and microorganisms. Plant growth and architecture of entire plant, in fact depends upon the roots which provide sufficient amount of nutrients and water. Root tips while sensing the rhizosphere for availability nutrients counteract with array of harmful microorganisms in the soil. In order to protect from these stresses plant roots have evolved specialized cells known as root border cells which act as front line defence mechanism in rhizosphere. Border cells are individual or bunch of programmed viable cells released from root tip which forms protective sheath between root and external environment. Border cells secret hydrated mucilage that contains antimicrobial compounds and extracellular DNA which governs the behaviour of microbiome in the soil. Production of border cell is regulated by number of factors such as phytohormones, PME enzyme and transcription factor NLP7. Plant breeding and genetic engineering could be used to exploit border cells defence mechanism as a new avenue for disease control. This review summarizes about the importance, properties of border cells, mechanism, and regulation of border cells production and role of RETs as element of plant defence.